2021
DOI: 10.1021/jacsau.1c00121
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atom Catalysts: A Perspective toward Application in Electrochemical Energy Conversion

Abstract: Single-atom catalysts (SACs) hold great promise for maximized metal utilization, exceptional tunability of the catalytic site, and selectivity. Moreover, they can substantially contribute to lower the cost and abundancy challenges associated with raw materials. Significant breakthroughs have been achieved over the past decade, for instance, in terms of synthesis methods for SACs, their catalytic activity, and the mechanistic understanding of their functionality. Still, great challenges lie ahead in order to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 125 publications
0
59
0
Order By: Relevance
“… 82 Under the OER or ORR conditions, the carbon atoms in widely investigated Fe–N–C catalysts can be oxidized to CO or CO 2 . 12 Thus, according to the working conditions, criteria related to possible side reactions are expected to be provided to comprehensively evaluate the stability of SACs during the theoretical design of new SACs.…”
Section: Design Criteriamentioning
confidence: 99%
“… 82 Under the OER or ORR conditions, the carbon atoms in widely investigated Fe–N–C catalysts can be oxidized to CO or CO 2 . 12 Thus, according to the working conditions, criteria related to possible side reactions are expected to be provided to comprehensively evaluate the stability of SACs during the theoretical design of new SACs.…”
Section: Design Criteriamentioning
confidence: 99%
“…These properties, along with the increased number of under-coordinated metal atoms, i.e., the increased amount of active catalytic sites, make nanocluster catalysts highly active towards a wide range of chemical reactions, such as CO 2 RR and HER [22][23][24][25]. The ideal case, corresponding to the minimum size and the maximum metal-utilization of the nanocluster is represented by the metal single atom: at this size, individual metal atoms become accessible, and therefore active for catalysis [26]. More generally, in order to guarantee high dispersion and to avoid agglomeration, nanoparticle catalysts are typically dispersed on a support surface.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Among all identified PGM-free candidates, iron-nitrogen-doped carbon (Fe-N-C) is the most promising to catalyse the sluggish ORR. 6,7 Recent studies have theoretically and experimentally demonstrated that Fe-N-C catalysts are more active and stable in alkaline than in acidic media. [8][9][10] This indicates the unique possibility to use Fe-N-C as a relatively efficient, earth abundant and cheap cathode catalyst material in alternative anion exchange membrane fuel cell (AEMFCs) technology.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, understanding of Fe x+ leaching and consequent implementation of mitigation strategies to its suppression are considered main challenges. 6,8,15,16 So far, four key Fe-N-C degradation mechanisms have been suggested to occur in parallel or series in acidic media, 7 providing clues also to studies in alkaline electrolytes:…”
Section: Introductionmentioning
confidence: 99%